Whole exome sequencing identifies ABHD14A and MRNIP as novel candidate genes for developmental language disorder - Amal Bouzid; Malek Belcadhi; Amal Souissi; Meryam Chelly; Fakher Frikha; Hela Gargouri; Crystel Bonnet; Fida Jebali; Salma Loukil; Christine Petit; Saber Masmoudi; Rifat Hamoudi; et al. (Scientific Reports, 2025)
Abstract Developmental language disorder (DLD) is a neurodevelopmental disorder involving impaired language abilities. Its genetic etiology is heterogeneous, involving rare variations in multiple susceptibility loci. However, family-based studies on gene mutations are scarce. We performed whole-exome sequencing (WES) of a first-time-described Tunisian-family with DLD. Analyses of segregation patterns with stringent filtering of the exome data identified disease-causing compound heterozygous variants. In the MRNIP gene, two variants were detected including a synonymous low-frequency variant c.345G > C and a nonsense rare variant c.112G > A predicted pathogenic. In the ABHD14A gene, four variants were identified including a rare missense variant c.689T > G and three splice-site variants c.70-8C > T, c.282-25A > T and c.282-10G > C with low-frequency MAF < 5%. Complementary analyses showed that these variants are predicted pathogenic and the missense variant Leu230Arg significantly affects the stability and structure modelling of the ABHD14A protein. Biological functions and interconnections analyses predicted the potential roles of ABHD14A and MRNIP in neuronal development pathways. These results suggest ABHD14A and MRNIP, as putative candidate genes for DLD susceptibility. Our findings reveal the involvement of novel candidate genes in the genetic etiology of DLD and explore the potential future utility of WES in the diagnosis of such complex disorders.